Pandora's box the greed, lust, and lies that broke television - Biskind, Peter 1940- (Penguin Books, 2024)
An Economist book of the yerar; From The Sopranos to streaming: the scandalous behind-the-screens story of the TV revolution by the author of the cult film classic Easy Riders, Raging Bulls. The revolution has been televized. From The Sopranos to Stranger Things, the shows we watch - and the ways we watch them - have been transformed over the past fifty years. Out of the bland wasteland of 'play-it-safe' broadcasting came astonishing stories of sex, violence, and corruption shown first on cable, and then by way of streaming. Today, the power of viewers to select what they want and when they want it is greater than ever before. In short, we are living in a new golden age of television, but golden ages don't last forever. Revolutions have a habit of eating their own, and the era of 'peak TV' may have an unhappy ending. Pandora's Box is a major new account of the small screen from cultural critic Peter Biskind. Through exclusive, candid and colourful interviews with writers, showrunners, directors and actors, Biskind brings us face to face with the people whose creations we encounter every day on our sofas, and reveals the dynamic interplay of art, commerce and technology. We follow executives down the corridors of power and see how their money and guile cultivate, then crush creativity; we witness the making - and unmaking - of TVs biggest hits. There has never been a more exciting time in entertainment history, and Peter Biskind, the ideal insider guide, captures it all
Originally published: UK: Allen Lane, 2023
Keywords: Geschichte; Kabelfernsehen; Streaming -- Kommunikationstechnik; Fernsehsendung; USA; Television programs / United States / History; Cable television / United States / History